Histological and Chemical Studies of Goat Skin Transformation Processing of Raw Skin into Tanned Leather - Rahmawati, Atiqa; Putri, Naimah; Wibowo, Ari (Faculty of Agriculture, 2025)
Fresh goat skin and skins tanned with different tanning agents were prepared for histological, chemical, and physical analyses. Fresh skin samples were fixed in 10% formalin solution, processed using the paraffin embedding technique, sectioned, and stained with hematoxylin and eosin to determine the histological structure. Samples of goat tanned skin, treated with various tanning agents (chrome, aldehyde, chamois, and vegetable), underwent chemical analysis using Fourier Transform Infrared Spectroscopy (FTIR) followed by physical analyses, including tensile strength, tear strength, thickness, and shrinkage temperature. The results showed that the histological structure of fresh skin consisted of two layers: the epidermis and dermis, while tanned leather only exhibited the dermis layer. The epidermis was removed during the tanning process. FTIR analysis of chrome-tanned leather showed bands at 1633 cm1 (amide I), 1554 cm1 (amide II), and 1240 cm1 (amide III). Aldehyde-tanned leather showed bands at 1651 cm1, 1550 cm1, and 1271 cm1 (amide I, II, and III), while vegetable-tanned leather displayed bands at 1634 cm1 (amide I), 1552 cm1 (amide II), and 1239 cm1 (amide III). Shifts in peak positions, intensity, and the number of signature peaks were observed across the tanning agents (chrome, aldehyde, oil, and vegetable). The use of different tanning agentswet blue, wet white, vegetable-tanned, and chamoisresulted in distinct grain-surface structures, significantly influencing the physical characteristics of the leather.